The Relationship Between Corporate Governance Mechanisms and CSR Disclosure: Evidence from Jordanian’s Listed Firms - ALKHAZALIH, QUTAIBA; Shahbudin, Amirul; Ghazali, Aziatul (Journal of Public Administration and Governance, 2022)
The purpose of the current study is to examine the relationship between corporate governance mechanisms and corporate social responsibility disclosure in the Jordanian context. Research is quantitative in nature, based on panel data of 78 firms listed on the Amman Stock Exchange (ASE) for 8 years from 2012 to 2019, with 624 observations, To deal with an econometric problems such as heteroscedasticity and autocorrelation, the panel corrected standard error (PCSE) regression was used to assess the relationship among variables. The study found that board size affects positively CSR disclosure, while board independence and managerial ownership affect negatively CSR disclosure. On another hand, the study found that the presence female in board, CEO duality, family ownership, and concentration ownership do not affect CSR disclosure. Because of the chosen sample, the research results may lack generalisability to other country. Therefore, researchers are encouraged to test another sample. The study contributes to the understanding of how good corporate governance practices affect CSR disclosure for both academics and particularly Jordanian policymakers. This study provided new findings to bridge the gaps in the general corporate governance literature relative to the lack of consensus on the relationship between corporate governance mechanisms and CSR disclosure. The finding contributes to knowledge by providing new and original evidence that some current corporate governance mechanisms are not effective in increasing CSR disclosure in a developing setting.